PELATIHAN KELOMPOK PENDAMPING DIABETES SELF MANAGEMENT EDUCATION (KP-DSME) BERBASIS KELUARGA - Sitio, Roma; Nurleli, Nurleli; Afdhal, Afdhal; Taufik, Taufik; Syamsuddin, Asniah; Ritawati, Ritawati (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
Aceh ranks the 7th with the most diabetes mellitus in the whole of Indonesia. Success in the management of diabetes mellitus has severe challenges because it has to be lifelong, which often leads to nausea and disobedience. One important factor in promoting treatment in patients with diabetes mellitus is support from the family.The purpose of this community service is to increase the knowledge, skills and ability of the family in providing self-reliant care for the dm family members, to increase the knowledge and skill of the non-infectious disease of cadres in their readiness to provide help to the family of dm patients.This community service takes place at 3 (three) stages: socialization, demonstration, and monitoring and evaluation together with 10 (ten) cadre of non-infectious disease and families with diabetes 31.There are differences in knowledge, skill, and ability to provide self-reliant care for family members with diabetes mellitus, as well as increased knowledge and skill in providing family member readiness. Regular assistsof family members living in homes with diabetes patients is needed to control diet and physical exercise, as well as medical and cadres compliance to monitor and cooperate with the family DM.Socialization, demonstration and monitoring and evaluation can enhance our knowledge of the treatment of diabetes patients in cadres and family diabetes.